USE OF LEARNING VIDEO MEDIA ON HUMAN AND ENVIRONMENTAL SUBTHEMA - Elly Sukmanasa; Lina Novita; Rifki Abdul Majid (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2019)
This study aims to determine the effect of learning outcomes and improve learning outcomes of human and environmental sub-themes through instructional video media. The method used is a quasi experiment, carried out on students of class VA and VB SDN Gegerbitung Sukabumi. The analysis technique used is the analysis prerequisite test which includes a normality test, a homogeneity test, then a research hypothesis test is performed using the t test. The results showed that in the normality test both samples were normally distributed because of the L value â‰¤ Ltable. Then the homogeneity test obtained nilai2 count value of 0.26 â‰¤ ð‘¥2table 3,841, then: There is an influence of learning outcomes of human and environmental subthemes through instructional video media obtained an average value of N-Gain 61 with completeness of learning outcomes 94.44%, and conventional media obtained an average value of 42 N-Gain with completeness learning outcomes 63.15%. And the results of testing the hypothesis states that H0 is rejected and Ha is accepted because tcount (5.29) ttable (1.99346). Based on the results of the research above, it can be concluded that there is an influence of the learning outcomes of human and environmental sub-themes through instructional video media.